The Exploitation of Dar-Zarrouk Parameters to Differentiate Between Fresh And Saline Groundwater Aquifers of Sinjar Plain Area. - Al-Yasi, Ameen; Alridha, Nawal; Shakir, Wadhah (Iraqi Journal of Science, 2024)
This research discusses the exploitation of Dar-Zarrouk (D-Z) parameters whichwere deduced from the quantitative interpretation of 80 Schlumberger VerticalElectrical Sounding VES points distributed in six profiles within the Sinjar plainarea which bounded by the coordinates:Latitudes :35PoP 22P’P 00P’’P S – 36PoP 22P’P 00P’’P N ;longitudes : 41PoP 36P’P 00P’’PW – 43PoP 00P’P 00P’’P E. The VES field data were provided by theIraqi general commission of groundwater. The VES field readings were interpretedmanually by applying the (auxiliary point -partial resistivity curve matching)method, then the interpretation enhanced by using sophisticated computer software.The VES field data were interpreted and analyzed with an advanced techniquethrough the deduction of D-Z geoelectric parameters which are: Longitudinal unitconductance (S) and Transverse resistance (T), then a new geoelectric maps wereconstructed. The D-Z parameters maps were used to differentiate aquifers of freshgroundwater from those of saline ones. This technique reduced the ambiguity relatedto interpretation which mainly produced by principles of equivalence andsuppression and cause intermixing in recognizing depth limits for the electricalzones (fresh and saline water bearing formations) during interpretation. The drawingof (D-Z) and other geoelectric parameters maps provided a decipherable visionabout the occurrence and distribution of saline and fresh groundwater aquiferswithin the study area.